Tissue‐specific venous expression of the EPH family receptor EphB1 in the skin vasculature. Issue 8 (18th June 2013) - Li, Wenling; Mukouyama, Yoh‐suke
<x xml:space="preserve">Abstract</x> Background: The major arteries and veins are formed early during development. The molecular tools to identify arterial and venous endothelial cells improve our understanding of arterial–venous differentiation and branching morphogenesis. Compared with arterial differentiation, relatively little is known about what controls venous development, due to lack of definitive molecular markers for venous endothelial cells. Results: Here we report that the antibody against EphB1, an EphB class receptor, makes it possible to establish a reliable whole‐mount immunohistochemical analysis of venous identity with greater resolution than previously possible in embryonic and adult skin vasculature models. EphB1 expression is restricted to the entire venous vasculature throughout embryonic development to adulthood, whereas the previously established venous marker EphB4 is also detectable in lymphatic vasculature. This venous‐restricted expression of EphB1 is established after the vascular remodeling of the primary capillary plexus has occurred. Compared with its venous‐specific expression in the skin, however, EphB1 is not restricted to the venous vasculature in yolk sac, trunk and lung. Conclusions: These studies introduce EphB1 as a new venous‐restricted marker in a tissue‐specific and time‐dependent manner. Developmental Dynamics 242:976–988, 2013. © 2013 Wiley Periodicals, Inc.